2010
DOI: 10.1016/j.ijgo.2009.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Anal dilation during labor

Abstract: Anal dilation during the second stage of labor causes anthropometric changes to the perineum. This ought to be considered when designing anthropometric studies and in studies aiming at minimizing anal sphincter trauma during delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Table 1 shows the studies involving PL measurements antenatally, and in the first and/or second stage of labour. The average PL is 39 mm (range 37-41 mm) in the late antenatal period or first stage of labour [26][27][28][29][30][31] and PL has increased by 50-60 % at crowning to 60 mm [31][32][33]. Patients with PL ≤25 mm (measured during the first stage) had a significantly greater risk of OASI (40 % vs. 5.6 %, p= 0.004) [26].…”
Section: Anatomical and Tissue Factors Perineal Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the studies involving PL measurements antenatally, and in the first and/or second stage of labour. The average PL is 39 mm (range 37-41 mm) in the late antenatal period or first stage of labour [26][27][28][29][30][31] and PL has increased by 50-60 % at crowning to 60 mm [31][32][33]. Patients with PL ≤25 mm (measured during the first stage) had a significantly greater risk of OASI (40 % vs. 5.6 %, p= 0.004) [26].…”
Section: Anatomical and Tissue Factors Perineal Lengthmentioning
confidence: 99%
“…The biomechanics of birth have been studied by clinical observation [33,35,36], MRI studies [39] and stereophotogrammetry [21]. The anal orifice has been found to dilate to 25 mm in the anteroposterior and transverse diameters during crowning, implying a circular dilatation [33].…”
Section: Perineal Deformation/distensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on stereo‐photogrammetric analysis of perineal deformation during fetal head expulsion, MPP seems to produce its protective effect via dispersion of the highest perineal tension over a wider surface area. This is mainly achieved by a reduction in the transverse perineal tension using the accoucheur’s thumb and index finger alongside the vaginal opening . Subsequent computational biomechanical studies showed that such maneuver can produce up to a 30% reduction in relative tension in the perineal region, dependent on the precision of its execution .…”
Section: Introductionmentioning
confidence: 99%
“…We agree that the perineal body length and the type of episiotomy are two independent obstetric variables. This was already addressed in one of our recent studies 2 . However, our article in BJOG aimed to draw attention to a careful description of the types of episiotomy described in scientific articles, and proposed a clear classification of the different types 3 .…”
Section: Authors’ Replymentioning
confidence: 93%